SIMULASI GERAK OSILASI PAKSA DENGAN REDAMAN MENGGUNAKAN SPREADSHEET EXCEL DAN MACRO VISUAL BASIC FOR APPLICATION - Rosliana Eso (Jurnal Aplikasi Fisika, 2017)
This paper discus about the forced oscillation with damping which it is simulated by using Excel Spreadsheet and Macro Visual Basic For Application.  The system was considerating  as a string with mass m  where it oscillates on  the influence of force and damp. The Equations of forced oscillation with damping processes  in spreadsheet excel and  simulates  using  Macro Visual Basic For Application approached.  To verify the accuracy  we use  the numerical solution of Heun and Runge-Kutta Merson methods, the two-order differential equations are converted to first order linear differential equations and then look for algorithms for each numerical method. Algorithm of numerical method of input, process and output.  This paper also shows that Runge-Kutta Merson  numerical method has higher accuracy than Heun numerical method in solving the equation of forced oscillation with damping.Keywords: Numerical Solutions, Excel Spreadsheet,  Visual Basic For Application